2021
DOI: 10.1093/europace/euab160
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring data from cardiac implantable electronic devices predicts all-cause mortality

Abstract: Aims To determine if remotely monitored physiological data from cardiac implantable electronic devices (CIEDs) can be used to identify patients at high risk of mortality. Methods and results This study evaluated whether a risk score based on CIED physiological data (Triage-Heart Failure Risk Status, ‘Triage-HFRS’, previously validated to predict heart failure (HF) events) can identify patients at high risk of death. Four hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Remote monitoring can deliver information from an enormous number of patients and provide the scientific community with important data regarding arrhythmias, heart failure, sudden cardiac death, and all-cause mortality. This has been described in several studies [ 26 , 27 , 28 , 29 , 30 ] and also discussed in previous reviews [ 31 ].…”
Section: Safetysupporting
confidence: 67%
“…Remote monitoring can deliver information from an enormous number of patients and provide the scientific community with important data regarding arrhythmias, heart failure, sudden cardiac death, and all-cause mortality. This has been described in several studies [ 26 , 27 , 28 , 29 , 30 ] and also discussed in previous reviews [ 31 ].…”
Section: Safetysupporting
confidence: 67%
“…LGE-CMR), 68 monitoring (e.g. remote monitoring) 69 or therapeutic (e.g. ablation) 62 technologies for patients at risk of SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Spending ≥1 day in a high-risk status was associated with a 3.07 increase in the odds risk of death (95% CI [1.57-6.58]; p=0.002), with a correlation observed between the number of days in a high-risk status and the risk of death. 68 Zile et al reported that 4-year all-cause mortality rates for high-and low-risk status patients (maximum score within the first 6 months of score initialisation) was 38% and 14%, respectively. 66 The TriageHF risk status has been tested in combination with a clinical pathway in various small-scale clinical studies.…”
Section: Medtronic Triagehf Risk Statusmentioning
confidence: 99%